"It's a life you're playing with": A qualitative study on experiences of NHS maternity services among undocumented migrant women in England. (February 2021) - Nellums, Laura B.; Powis, Jaynaide; Jones, Lucy; Miller, Anna; Rustage, Kieran; Russell, Neal; Friedland, Jon S.; Hargreaves, Sally
Abstract: Background: Undocumented migrant women experience complex barriers to maternity services, are less likely to receive the recommended level of maternity care, and have poorer obstetric outcomes than non-migrant women. There are concerns increasing restrictions on entitlement to health services have a detrimental impact on access to services and obstetric outcomes, particularly among undocumented migrant women. The study aimed to investigate the experiences of undocumented migrant women who have been pregnant in England, and factors affecting access to care and health outcomes. Methods: We conducted in-depth semi-structured interviews June–December 2017 with a purposive sample of migrant women born outside the UK (aged>18) who had experiences of pregnancy and undocumented status (without permission to reside) in the UK, recruited through Doctors of the World (DOTW) UK. Interpreting services were used on request. Interviews were recorded, transcribed, and analysed using thematic analysis. Ethical approval: Imperial College London Research Ethics Committee (ICREC reference: 17IC3924). Results: Semi-structured interviews were conducted with 20 participants, 10 of whom had their first antenatal appointment after the national target of 13 weeks, and nine of whom reported complications. Themes defining women's experiences of pregnancy included: restricted agency, intersecting stressors, and an ongoing cycle of precarity, defined by legal status, social isolation, and economic status. Conclusions: This study provides new evidence of women's experiences of pregnancy in the UK in the context of increasingly restrictive health policies including charging and data sharing. Six recommendations are made to ensure the UK and other migrant receiving countries work towards reducing inequalities and achieving national and global targets for maternal and child health and universal health coverage. Highlights: Undocumented migrant women not entitled to free NHS England maternity services. Half of women interviewed experienced delays in accessing NHS maternity services. Key themes included restricted agency, stressors, and a cycle of precarity. Six immediate recommendations for policy and practice are drawn from the findings.